Pengaruh Pengawasan Terhadap Implementasi Kebijakan Izin Mendirikan Bangunan Di Kabupaten Deliserdang - SitorusÂ , Monang (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2014)
The aim of this research is to analyze the inï¬‚uence controlling towards policy implementation building ooniruction permission (Case studyofRegency Deli Serdang). Thetheory ofoontrolling tested out by the writerbyRobbins and Coulter (2006) wich consists of three dimension namely (1). standars, (2). measurements and comparison (3) action. The theory performance tested out by the writer by Iones (1994:166) dimension (1). organization (2). interpretation (3). aï¬‚ication. 'D1ese three dimension were applied by the to analysis policy implementation building amtruction permission in Regency Deliserdang. To inden tify the three inï¬‚uenceof dimension, a survey approach was conducted through a proportional sample of 130 head of household (informants). The data were analyzed by using Path Analysis, in the program SPSS. The value was found out eadi dimensions as follows; (a). inï¬‚uence standars ( X) to policy implementation building contruction permission (Y) is 26.53% (low category), inï¬‚uense measurements and comparison (X) topolicy implementation building contruction permission (Y) is 16.19% (low category), inï¬‚uense action (X) topolicy implementation building contruction permission (Y) is 33.86% (medium category). Theeï¬izct ( X,,X,,X,) to Y is 76.58% (strong category, and the residu is 23.42% inï¬‚uenced theother dissimilar factor (epsilon).